2007
DOI: 10.1080/01421590701299256
|View full text |Cite
|
Sign up to set email alerts
|

Use of 360-degree assessment of residents in internal medicine in a Danish setting: a feasibility study

Abstract: The method was practical in busy clinical departments and was well accepted by the assessors. Reliability of the method was acceptable. It discrimintated satisfactorily between the good and not so good performers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 6 publications
0
10
0
7
Order By: Relevance
“…resident 360-degree evaluation without the loss of any important information is possible. Of note, although our original tool, at 19 items, seemed lengthy, and this concern was the impetus for conducting the current study, it was not unusually long compared to those reported elsewhere in the literature, which ranged from 3 to 98 items 7Y16 One Danish study reported a median survey completion time of 14.5 mins (for 22 items), 17 which is probably impractical in some settings.…”
Section: Discussionmentioning
confidence: 91%
“…resident 360-degree evaluation without the loss of any important information is possible. Of note, although our original tool, at 19 items, seemed lengthy, and this concern was the impetus for conducting the current study, it was not unusually long compared to those reported elsewhere in the literature, which ranged from 3 to 98 items 7Y16 One Danish study reported a median survey completion time of 14.5 mins (for 22 items), 17 which is probably impractical in some settings.…”
Section: Discussionmentioning
confidence: 91%
“…Multi-source feedback (MSF) is a questionnaire-based assessment and feedback process widely used in medical education in the UK and other countries, and proposed for all UK doctors as part of revalidation (Wood et al 2006;Allerup et al 2007; Secretary of State for Health 2007; Davies et al 2008;Bullock et al 2009). The aim of MSF, framed within constructivist and quality improvement perspectives, is to help raise learners' and doctors' insight and self-awareness of their clinical and professional capabilities, thereby leading to learning and performance improvement (Goodstone & Diamante 1998;Norcini & Burch 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Similar efforts have been made in other jurisdictions around the world 14,15 . However, most literature about the CanMEDS competencies focuses on the psychometric properties of individual assessment tools and implementation of the core competencies in a specific specialty, rather than the systemic integration of assessment tools in resident evaluation across specialties 16–20 . Little is known about how the CanMEDS competencies are currently assessed in Canadian postgraduate training programmes.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 However, most literature about the CanMEDS competencies focuses on the psychometric properties of individual assessment tools and implementation of the core competencies in a specific specialty, rather than the systemic integration of assessment tools in resident evaluation across specialties. [16][17][18][19][20] Little is known about how the CanMEDS competencies are currently assessed in Canadian postgraduate training programmes. In an attempt to address this issue, Ruedy 21 conducted a study evaluating the process of resident in-training evaluation with particular reference to CanMEDS roles at a single Canadian medical school and found that the overall perceived effectiveness of the evaluation process in assessing CanMEDS roles varied considerably, with evaluation for the roles of Medical Expert and Communicator perceived as most effective, and that for Health Advocate and Professional as least effective.…”
Section: Introductionmentioning
confidence: 99%